GUIDANCE AND COUNSELING SERVICES TO DEVELOP A SPIRIT FOR LEARNING IN EARTHQUAKE VICTIM CHILDREN - Muhammad Rezza Septian (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
This research is motivated by the lack of provision of guidance and counseling services at the early childhood level. The lack of enthusiasm for learning in children is also easily felt, so various methods or techniques are needed to help develop children's enthusiasm for learning at an early age level by carrying out guidance service activities. and appropriate counseling for early childhood. Reviewing this, the results obtained are that the implementation of early childhood guidance and counseling services in developing enthusiasm for learning can use the collaboration of various techniques or methods such as games and storytelling and is also supported by the provision of attractive service media so that children do not quickly feel bored or bored when delivering service takes place. This research was conducted using a descriptive qualitative approach with data collection techniques, interviews and observations